Regulation of fruit colour development, quality and storage life of Hibiscus sabdariffa L. as influenced by plant growth regulators - Kek, T. Z.; Sakimin, Siti Zaharah; Juraimi, Abdul Shukor; Nazrin, M.; Alam, Md. Amirul; Aslani, Farzad (Bangladesh Botanical Society, 2017)
The physico-chemical properties of abscisic acid (ABA) and IAA treated roselle calyces stored in different storage temperature was determined in this study. Mature roselle was dipped in distilled water (control),10-4 mol/l of ABA and 10-4mol/l of IAA for 5 minutes. All treated calyces were kept at ambient temperature (23°C) for 4 days, or stored at cold storage (10°C) for 8 days. Low temperature (10°C) can prolong the shelf life of roselle about 4 days longer than ambient storage (23°C). However, plant growth regulator (ABA or IAA) only showed minimal effect on quality and shelf life of roselle. Therefore,the application of higher concentration of ABA or IAA as well as dipping for more than 5 minutes can influence the postharvest quality and shelf life of roselle calyces, respectively.